2006
DOI: 10.1186/1471-2458-6-122
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne microbial risk assessment : a population-based dose-response function for Giardia spp. (E.MI.R.A study)

Abstract: Background: Dose-response parameters based on clinical challenges are frequently used to assess the health impact of protozoa in drinking water. We compare the risk estimates associated with Giardia in drinking water derived from the dose-response parameter published in the literature and the incidence of acute digestive conditions (ADC) measured in the framework of an epidemiological study in a general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…However, this is unsupported, since many long-term infections are suspected to represent either persisting abdominal symptoms elicited post-Giardia infection or reinfections (176,196,484). The fecal-oral route still remains the most important mode of infection (33), and various studies have found evidence of zoonotic transmission (89,118,237).…”
Section: Giardia Intestinalismentioning
confidence: 99%
“…However, this is unsupported, since many long-term infections are suspected to represent either persisting abdominal symptoms elicited post-Giardia infection or reinfections (176,196,484). The fecal-oral route still remains the most important mode of infection (33), and various studies have found evidence of zoonotic transmission (89,118,237).…”
Section: Giardia Intestinalismentioning
confidence: 99%
“…The parameter b i represents the site-dependent rate of exposure to contaminated water, and f(B i ) is the probability of becoming infected because of the exposure to a concentra-tion B i of pathogens. The dose-response function f (B i ) (Zmirou-Navier et al 2006) usually saturates for high pathogen concentrations. Beta-Poisson, exponential, and hyperbolic are the most-used models.…”
Section: The Modelmentioning
confidence: 99%
“…Data from SCADA systems allow for the detailed investigation of events through the analysis of the distributed monitoring data and reporting of control actions. fold) discrepancies between advanced inactivation models (Zhang et al 2006;Brosé us et al 2006). Major issues with treatment models which remain unresolved include: (1) the lack of established validation with inactivation/treatment data from full-scale plants which include actual operational data (SCADA); (2) the inability of these models to fully take into account the impact of water quality (Mysore et al 2003;Hijnen et al 2004;Barbeau et al 2004Barbeau et al , 2005 and the initial pathogen concentration (Haas & Kaymak 2002.…”
mentioning
confidence: 99%